IMPLEMENTASI ALAT PERMAINAN EDUKATIF RUMAH PINTAR KAJANG LAKO KHAS BUDAYA JAMBI PADA TK ISLAM DINIYYAH AL-AZHAR JAMBI - Annisa Bondhowati; Anisya Fitri; Bunga Isrotul Hasanah; Shella Noprida Yanti; Siti Mupadillah; Nyimas Muazzomi (STKIP Subang, 2025)
Early childhood education is an important stage in stimulating all aspects of child development, including cognitive, motor, socio-emotional development, as well as the cultivation of cultural values and character. This study aims to describe the implementation of the Rumah Pintar Kajang Lako Educational Play Tool (Alat Permainan Edukatif/APE) as a learning medium for introducing the traditional house culture of Jambi to children aged 5–6 years.This study employs a qualitative approach, with data collection techniques including literature review and observation of children’s play activities. The research subjects were 18 children from TK Islam Diniyyah Al-Azhar, Jambi City.The results show that the use of the Rumah Pintar Kajang Lako APE provides meaningful stimulation for children’s cognitive and fine motor development through activities such as assembling geometric puzzles, recognizing numbers 1–10, identifying typical Sumatran animals, and learning about distinctive cultural features of Jambi City, including traditional foods, the Keris Monument, and Gentala Arasy. These play activities also promote hand–eye coordination, thinking skills, memory, and problem-solving abilities.In addition, this APE is effective in instilling knowledge and appreciation of local culture from an early age. The role of the teacher as a facilitator, by providing guiding questions, further supports children’s exploration and active participation in the learning process. Therefore, the Rumah Pintar Kajang Lako APE can be used as an effective, enjoyable, and contextual alternative learning medium in early childhood education to support child development while preserving Jambi’s local culture.